(cosx+sinx)/cosx-sinx=tg2x+cos^-1(2x) докажите тождество

0 голосов
35 просмотров

(cosx+sinx)/cosx-sinx=tg2x+cos^-1(2x) докажите тождество


Алгебра (185 баллов) | 35 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

(cosx+sinx)/(cosx-sinx) = tg2x + 1/cos2x

(cosx+sinx)/(cosx-sinx) = sin2x/cos 2x + 1/cos2x

(cosx+sinx)/(cosx-sinx) = (sin2x + 1)/cos 2x

(cosx+sinx)/(cosx-sinx) = (sin2x + sin²x + cos²x)/cos 2x

(cosx+sinx)/(cosx-sinx) = (sinx + cosx)²/(cos²x - sin²x)

(cosx+sinx)/(cosx-sinx) = (sinx + cosx)·(sinx + cosx)/(cosx - sinx)(sinx + cosx)

(cosx+sinx)/(cosx-sinx) = (sinx + cosx)/(cosx - sinx)

(cosx+sinx)/(cosx-sinx) ≡ ( cosx + sinx)/(cosx - sinx)

(145k баллов)
0 голосов

\frac{cosx+sinx}{cosx-sinx}=tg2x+cos^{-1}2x

Будем работать с правой часть уравнения

tg2x+cos^{-1}2x=\frac{sin2x}{cos2x} + \frac{1}{cos2x}=\frac{sin2x+1}{cos2x}=\frac{cos^2x+sin^2x+2sinxcosx}{cos^2-sin^2}=\frac{(cosx+sinx)^{2}}{(cosx-sinx)(cosx+sinx)}=\frac{cosx+sinx}{cosx-sinx}

(4.9k баллов)